(untitled) (Hilo Analítico, 2023)
What does my son have? It is a question from many parents who come to the office so that the psychologist or psychoanalyst can solve it. However, it is an extremely complex question, since it requires a historical approach to the family and the relationship between father and son in order to resolve it. This approach, necessary to resolve the question, concern and preoccupation of the father, will inevitably mean that a question must be resolved, an unavoidable consequence of therapeutic work, namely, Was I a good son?